Characteristics of a Large Cohort of Patients with Autoimmune Pulmonary Alveolar Proteinosis in Japan - Inoue, Yoshikazu (American Thoracic Society, 2008)
Rationale: Acquired pulmonary alveolar proteinosis (PAP) is a syndrome characterized by pulmonary surfactant accumulation occurring in association with granulocyte/macrophage colony-stimulating factor autoantibodies (autoimmune PAP) or as a consequence of another disease (secondary PAP). Because PAP is rare, prior reports were based on limited patient numbers or a synthesis of historical data. Objectives: To describe the epidemiologic, clinical, physiologic, and laboratory features of autoimmune PAP in a large, contemporaneous cohort of patients with PAP. Methods: Over 6 years, 248 patients with PAP were enrolled in a Japanese national registry, including 223 with autoimmune PAP. Measurements and Main Results: Autoimmune PAP represented 89.9% of cases and had a minimum incidence and prevalence of 0.49 and 6.2 per million, respectively. The male to female ratio was 2.1:1, and the median age at diagnosis was 51 years. A history of smoking occurred in 56%, and dust exposure occurred in 23%; instances of familial onset did not occur. Dyspnea was the most common presenting symptom, occurring in 54.3%. Importantly, 31.8% of patients were asymptomatic and were identified by health screening. Intercurrent illnesses, including infections, were infrequent. A disease severity score reflecting the presence of symptoms and degree of hypoxemia correlated well with carbon monoxide diffusing capacity and serum biomarkers, less well with pulmonary function, and not with granulocyte/macrophage colony-stimulating factor autoantibody levels or duration of disease. Conclusions: Autoimmune PAP had an incidence and prevalence higher than previously reported and was not strongly linked to smoking, occupational exposure, or other illnesses. The disease severity score and biomarkers provide novel and potentially useful outcome measures in PAP.